INTENSITAS PENGGUNAAN APLIKASI TIKTOK TERHADAP PERILAKU IMITASI REMAJA (Lembaga Penerbitan Universitas Esa Unggul, 2021)
The purpose of this study was to determine whether there is an effect of the intensity of the use of the TikTok application on the imitation behavior of adolescent students at SMAN 1 Jampangkulon, Sukabumi City. The research methodology used quantitative descriptive with data collection using a closed questionnaire which was distributed to 93 respondents from a population of 1,269 people using the Slovin formula. The research theory uses the Stimulus-Organism-Response (SOR) theory proposed by Hovland, et al. The data processing technique was performed using SPSS 16 with data analysis using descriptive analysis, normality test, simple linear regression test, and hypothesis testing. The results showed that Ha was accepted, meaning that the intensity of the use of the TikTok application affected imitation behavior in students. The result of the coefficient of determination on the r square value is 48.2%, while the remaining 57.2% is influenced by other factors not examined in the study, so it can be concluded that the intensity of using the TikTok application on imitation behavior in students has a moderate effect.